(untitled) (KULT_online, 2011)
This introductory book by Michael Braun offers access to the complex set of problems concerning the widespread and hardly limitable field of German contemporary literature. Helpful orientation is provided through informative looks at the arts sector, contemporary prose, verse, and film, but also in the form of commentated literature and online resources. Unfortunately, the introduction does not convince completely: often times the period under study, from 1968 until the present, seems to be too broad; the problems of important terms like ’canon’ or ’representativeness,’ furthermore, are not expounded upon.